We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**+1 **

\(y=-12\)

\(5(y+2)=2(2y-1)\) | This is the given equation. First, distribute the 5 and 2 |

\(5y+10=4y-2\) | Subtract 4y on both sides |

\(y+10=-2\) | Subtract 10 on both sides |

\(y=-12\) | We found y, so we are done! |

If you are ever unsure whether or not your answer is correct, plug the y-value into the equation. Then, check to see that the equation is true:

\(5(-12+2)=2(2(-12)-1)\) | Check to see if this is true by simplifying. Let's clean this up |

\(5*-10=2(-24-1)\) | |

\(5*-10=2*-25\) | |

\(-50=-50\) | This is true, so the answer, y=-12 is the correct and only correct solution |

TheXSquaredFactor May 23, 2017